Quantum spin Hall state in monolayer 1T'-WTe2 - Tang, Shujie; Zhang, Chaofan; Wong, Dillon; Pedramrazi, Zahra; Tsai, Hsin-Zon; Jia, Chunjing; Moritz, Brian; Claassen, Martin; Ryu, Hyejin; Kahn, Salman; Jiang, Juan; Yan, Hao; et al. (Nature physics, 2017)
A combination of photoemission and scanning tunnelling spectroscopy measurements provide compelling evidence that single layers of 1T'-WTe 2 are a class of quantum spin Hall insulator. A quantum spin Hall (QSH) insulator is a novel two-dimensional quantum state of matter that features quantized Hall conductance in the absence of a magnetic field, resulting from topologically protected dissipationless edge states that bridge the energy gap opened by band inversion and strong spin–orbit coupling 1 , 2 . By investigating the electronic structure of epitaxially grown monolayer 1T'-WTe 2 using angle-resolved photoemission (ARPES) and first-principles calculations, we observe clear signatures of topological band inversion and bandgap opening, which are the hallmarks of a QSH state. Scanning tunnelling microscopy measurements further confirm the correct crystal structure and the existence of a bulk bandgap, and provide evidence for a modified electronic structure near the edge that is consistent with the expectations for a QSH insulator. Our results establish monolayer 1T'-WTe 2 as a new class of QSH insulator with large bandgap in a robust two-dimensional materials family of transition metal dichalcogenides (TMDCs).